De-biasing democracy. Behavioural public policy and the post-democratic turn. Issue 3 (2nd April 2020) - Strassheim, Holger
ABSTRACT: This article focuses on the political implications of behavioural public policy for democratic governance and participation. It is being argued that it is an influential case illuminating the way post-democratic practices gain global authority and redefine democracy and citizenship. The article is based on two assumptions: First, the rise and spread of behavioural public policy can only be understood as the result of global interactions. Second, behavioural experts manage to combine both political and epistemic authority. Based on randomized controlled trials as seemingly unquestionable evidence, behavioural insights are already feeding into the debate on the reasoning failures of citizens and the replacement of democracy by an epistocracy, i.e. a government of experts. While the behavioural discourse has informed critical reflections on deliberative democracy, proponents should be well aware of the post-democratic biases it has mobilized.